ANALISIS PENYIRAMAN AIR KERAS KEPADA NOVEL BASWEDAN DALAM TINJAUAN PEMIKIRAN ETIKA BURRHUS FREDERIC SKINNER (Jurnal Nawala Politika, 2023)
On April 11 2017, while walking home after morning prayers at the mosque, former KPK chairman Novel Baswedan was suddenly doused with acid by two unknown men riding a motorbike. Since then, Novel has undergone a series of treatments to heal his eyes. Since 2017, the police have formed a team containing hundreds of personnel from the police, regional police assisted by the National Police Headquarters. However, the team's independence is in doubt and it is thought that it will not have a significant impact on the development of Novel's case. The management of the joint team is dominated by police officials, from the National Police Chief, General Tito Karnavian, to the Deputy Chief of Metro Jaya Police, Brigadier General Wahyu Hadiningrat. According to Burrhus Frederic Skinner, the